Osteoarthritis Biomarkers and Treatments - Toumi, Hechmi; Mazor, Marija (Rheumatology, 2019)
This book presents exclusive and comprehensive insight into the detailed molecular mechanisms of osteoarthritis (OA) initiation, progression and current advancements in the field. Inputs from clinician scientists, research and expertise offer a complete explanation of the current understanding of the pathogenesis of OA and practice in imaging and treatments strategies. Contributions from leading scientists provide a detailed introduction in the use of biomarkers in clinical research as well as in clinical practice and OA diagnosis. This book further discusses the potential of regenerative therapies and recent advances in cardiovascular and functional capacity on patients with OA.